2002
DOI: 10.1097/00019052-200202000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The neuroanatomical basis of oculomotor disorders: the dual motor control of extraocular muscles and its possible role in proprioception

Abstract: Current investigations show that two separate sets of motoneurons control the extraocular eye muscles, and that is there is a dual final common pathway. We propose that one set of motoneurons are the major source of tension generating eye movements, whereas the other may participate in a proprioceptive system concerned more with the exact alignment and stabilization of the eyes. In this article we discuss the structures that may participate in the proprioceptive circuits; and consider several recent publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 76 publications
2
20
1
3
Order By: Relevance
“…Thus they may participate in a proprioceptive system important for setting and stabilising the alignment of the eye. 46 However, due to slower conduction and execution time the motor responses mediated by this system could be expected to occur at longer latencies as the responses in the current study.…”
Section: Proprioceptive Reflexes Of the Extraocular Musclesmentioning
confidence: 64%
“…Thus they may participate in a proprioceptive system important for setting and stabilising the alignment of the eye. 46 However, due to slower conduction and execution time the motor responses mediated by this system could be expected to occur at longer latencies as the responses in the current study.…”
Section: Proprioceptive Reflexes Of the Extraocular Musclesmentioning
confidence: 64%
“…They may be the principal source of proprioceptive feedback from extraocular muscles (19,20), although as with muscle spindles, this has been disputed (21).…”
Section: Extraocular Muscle Receptorsmentioning
confidence: 99%
“…Based mainly on animal studies, Buttner-Ennever et al (20,23) have suggested that each layer of the extraocular muscles has its own type of sensory receptor to generate afferent signals, with the orbital layer utilizing muscle spindles and the global layer relying on palisade endings. These investigators also suggest that sensory signals from palisade endings form part of a proprioceptive feedback network that modulates the non-twitch motor neurons that innervate the slow non-twitch extraocular muscles fibers.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…From palisade endings in extraocular muscle. 4 Although the precise function of these putative proprioceptive endings is a topic of debate, and the particular pathways by which they might influence the neural integrator not completely specified, the general proposition that information about muscle state is important for accurate eye-velocity commands seems very plausible. A fault in the proprioceptive input to the neural integrator might well produce nystagmus, and indeed modulation of proprioceptive input has been suggested as an explanation for the beneficial effects of horizontal rectus tenotomy on EON.…”
Section: Underlying Neuroanatomymentioning
confidence: 99%